Light fractionated ALA-PDT enhances therapeutic efficacy in vitro; The influence of PpIX concentration and illumination parameters - De Bruijn, Henriëtte S. (2013)
Light fractionation, with a long dark interval, significantly increases the response to ALA-PDT in pre-clinical models and in non-melanoma skin cancer. We investigated if this increase in efficacy can be replicated in PAM 212 cells in vitro. The results show a significant decrease in cell survival after light fractionation which is dependent on the PpIX concentration and light dose of the first light fraction. This study supports the hypothesis that an underlying cellular mechanism is involved in the response to light fractionation in which a first light fraction leads to sub-lethally damaged cells that are sensitised to a second light fraction 2 hours later. The current study reveals the in vitro circumstances under which we can investigate the cellular pathways involved.